Peran Ulama Perempuan Pesantren dalam Transformasi Dakwah Digital Era Media Sosial - Rummanah Himin; Ulya Fikriyati; Abd Warits; Mohammad Faizul Husnayain (JSP: Jurnal Studi Pesantren, 2023)
The role of female Islamic scholars from pesantren has expanded significantly into the public sphere, particularly in digital da'wah through social media platforms. In the globalization era characterized by religious misinformation and misunderstanding of Islam, pesantren female ulama have emerged as influential voices in contemporary Islamic discourse. This research examines the strategies employed by pesantren female ulama in digital da'wah and analyzes the prospects of their social media presence. Employing ethnographic field research methodology, this study collected data through documentation, in-depth interviews, and social media observation of three prominent pesantren female ulama: Ning Umi Laila, Ning Sheila Hasina, and Ning Imaz Fatimatuz Zahrah. Data analysis utilized data reduction, data display, and conclusion verification techniques, grounded in da'wah strategy theory and gender equality framework. The findings reveal that pesantren female ulama employ two primary da'wah strategies: sentimental strategy (al-Manhaj al-'Athifi) targeting emotional engagement, and rational strategy (al-Manhaj al-'Aqli) emphasizing logical reasoning. These strategies are adaptively implemented based on audience characteristics, selecting appropriate methods and materials aligned with the cognitive capacity of their followers (mad'u). The prospects of digital da'wah demonstrate significant reach and engagement, with Ning Umi Laila achieving 36.9 million views and 1 million followers, Ning Sheila Hasina reaching 2.3 million views with 611,000 followers, and Ning Imaz Fatimatuz Zahrah obtaining 410,200 views with 350,000 followers. This study contributes to understanding the transformation of traditional Islamic da'wah into digital formats and highlights the strategic role of female religious authorities in contemporary Muslim societies.